AN IMPROVED SEARCH ALGORITHM FOR SOLVING MIXED-INTEGER NON LINEAR PROGRAMMING PROBLEM - Pengarapen bangun et al. (Proceedings of ICMSA, 2005)
The special nonlinear mathematical programming problem which isaddressed in this paper has a structure characterized by a subset ofvariables restricted to assume discrete values, which are linear andseperable from the continuous variables. The strategy of releasingnonbasic variables from their bounds, combined with the